The unconstitutionality of preventive detention in police stations (2018)
Considering the deprivation of liberty in penitentiaries and prisons as an unconstitutional state of affairs, as stated multiples times by the Constitutional Court, permanent deprivation of liberty in police stations and URI’s presumes an aggravated infri